Pengaruh Word Of Mouth, Media Sosial, Dan Harga Terhadap Keputusan Pembelian Pada Mixue Di Kota Medan - Denni, Denni; Huliman, Huliman; Laudette, Willy (Innovative: Journal Of Social Science Research, 2024)
This study aims to look at the effect of word of mouth, social media, and price on purchasing decisions at Mixue Medan. The research methodology used is quantitative descriptive method. the type of data used is quantitative data, namely data obtained in the form of numbers or numbers. Data sources are primary data and secondary data. Primary data obtained from the results of distributing questionnaires to respondents, secondary data obtained from previous data or literature studies. The population used in this study were all Mixue consumers. The sampling technique used was the Lemeshow formula for an unknown population with a tolerance of 10% so that 97 respondents were obtained. Data testing is done by testing validity, reliability, classical assumptions, and hypothesis testing. The results showed that word of mouth has no effect and is partially significant on purchasing decisions. Social media has a positive and partially significant effect on purchasing decisions. Price has a positive and significant partial effect on purchasing decisions. Word of Mouth, Social Media, and Price have a simultaneous positive effect on purchasing decisions with a coefficient of determination of 44.2%.